Conceptual Terminological Variation in the Translation of Normative Texts from Chinese to Spanish across Different Domains and Macro-textual Parameters - Vicens Catalá, Carmen (Sinología hispánica. China Studies Review, 2026)
This study focuses on the problems presented by conceptual terminological variation in legal translation from Chinese into Spanish, in order to observe the decision-making process at the micro-textual level. Legal language is anchored in general language, where polysemy is “a norm in language”, its existence contributing to legal language being considered ambiguous, obscure and vague. Moreover, the same concept in the source language may have different meanings and uses in the target language, depending on its context and legal domain. Thus, as a point of departure, we have translated various laws of the People’s Republic of China belonging to different domains. These translations constitute the textual corpus in which we detect and analyse problematic terms due to their ambiguity or vagueness through various situational factors and macro-textual parameters for decision-making at the micro-textual level. The work is based on the framework of the communicative theory of terminology, so that it analyses the terms in vivo and the terminological variations in context.